Peningkatan Kebugaran Jasmani melalui Diseminasi Program Pengembangan Olahraga Senam Aerobik - Nurul Hikam Arifah; Lailatul Rohmah; Muhammad Naufal Anditya Santoso; Defi Wulan Rachmati; Ilma Suryana; Yetty Septiani Mustar (Inspirasi Nusantara, 2022)
Putat Jaya village still has the potential to improve physical fitness even with limited open space. Increased physical fitness can be achieved through one of the familiar sports, such as aerobics. The method approach used in this community service activity modifies the Participatory Rural Appraisal (PRA) strategy. The purpose of this PRA method is to invite the community to participate in the process of building and developing aerobic exercise activities in Putat Jaya Village. The results of the implementation of the activities that have been conducted showed that the community's enthusiasm for participating in the entire series of exercises is excellent. The community also considered that the facilitator delivering the method, the benefits of gymnastics, and the interaction of the facilitator with the community during aerobic exercise were magnificent and interactive. The awareness and independence shown by the residents of Putat Jaya Village in carrying out aerobic exercise activities positively impact the development of physical components and movement abilities, muscle endurance, strength, flexibility, coordination, agility, and body balance. Through this activity, the community has begun to understand the importance of exercising, particularly aerobics, in maintaining health and fitness. Additionally, the community is committed to regularly carrying out aerobic exercise activities.